2010
DOI: 10.1111/j.1095-8649.2010.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Spawning frequency of brood dams and sires in a marine fish stock‐enhancement hatchery

Abstract: Parentage analysis, employing five hypervariable microsatellite markers, was used to follow spawning patterns of red drum Sciaenops ocellatus broodfish in two spawning tanks through most of a calendar year in a marine fish hatchery dedicated to stock enhancement. Five of six dams and all four sires spawned at least once during the year. Variation in dam and sire spawning incidence and in number of progeny produced per dam and per sire translated into reduced genetic effective size (N e) per spawn by 40·6% in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…The markers will also facilitate the improvement of aquaculture programs through a variety of applications. For aquaculture facilities producing larvae that are subsequently grown for future sale, parentage assignments (Gold et al 2010) can identify broodstock contribution and can be used to maximize mating design and output. Differences in microsatellite allele sizes between species can be used to authenticate the labeling of aquaculture products as they go to market (Iguchi et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The markers will also facilitate the improvement of aquaculture programs through a variety of applications. For aquaculture facilities producing larvae that are subsequently grown for future sale, parentage assignments (Gold et al 2010) can identify broodstock contribution and can be used to maximize mating design and output. Differences in microsatellite allele sizes between species can be used to authenticate the labeling of aquaculture products as they go to market (Iguchi et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear-encoded microsatellites are useful markers for elucidating stock structure of "wild" fish (Miller et al 2011) and can contribute to fisheries management decisions (Reiss et al 2009). Microsatellites also are valuable for use in aquaculture programs, as they can serve as tools for parentage assignments (Gold et al 2010), species authentication (Iguchi et al 2012), and marker-assisted selection in "farmed" fish (Liu and Cordes 2004). In this paper, we evaluate the amplification of 31 microsatellites developed from the genomic DNA of greater amberjacks for cross-amplification in lesser amberjacks, yellowtail jacks, almaco jacks, and banded rudderfish.…”
mentioning
confidence: 99%
“…Within this context, there are two main points in the stock-enhancement timeline at which the genetic diversity of the stocked population can be negatively affected: spawning and rearing. In the former case, a high degree of variance in reproductive success (for instance, due to some broodfish not participating in spawning or otherwise contributing little to spawns) can lead to a low number of effective breeders and low effective population size (N e ; Gold et al 2008Gold et al , 2010Saillant et al 2009). In the latter case, the N e of the released population can be negatively impacted in the event that there is high mortality in the grow-out phase, and in particular if mortality affects one or more family groups disproportionately.…”
mentioning
confidence: 99%
“…In any stock enhancement situation, there is an expected loss of genetic diversity in the hatchery population relative to wild populations at the spawning phase, due to the constraints of spawning the hatchery population using a finite number of parental broodfish. Such losses to genetic variation in Red Drum have been characterized previously (Gold et al , 2010Saillant et al 2009). Gold et al (2010) demonstrated that further reduction in genetic diversity could be expected due to some broodfish contributing only marginally to annual spawns.…”
mentioning
confidence: 99%
See 1 more Smart Citation